Pengaruh Transparansi Komunikasi, Responsibility Individu, dan Akuntabilitas Individu Terhadap Penerapan Good Corporate Governance Ditinjau Dalam Perspektif Manajemen Sumber Daya Insani: Studi pada Karyawan Ayam Sambal Ladas di Kota Bandar Lampung - risalatulfatimah muawanah; Ahmad Habibi; Okta Suprianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of Good Corporate Governance (GCG) in practice still faces various challenges, particularly in the Micro, Small, and Medium Enterprises (MSME) sector, which plays a significant role in the national economy. Major obstacles arise from limited resources and organizational culture. In Lampung Province, there are 88,069 MSMEs recorded, dominated by Bandar Lampung City with 51,630 as of July 2025. One operating MSME in Bandar Lampung is Ayam Sambal Ladas, a culinary business established in 2019. The presence of MSMEs in Lampung's leading city in terms of quantity and growth offers a compelling research opportunity, especially in business management. This study focuses on the application of GCG principles at Ayam Sambal Ladas in its operations. By examining GCG implementation in growing MSMEs in this potential region, the research aims to illustrate how good governance can drive performance and sustainability of local culinary businesses. This study aims to analyze the influence of key individual-level GCG principles on GCG implementation from the perspective of Islamic Human Resource Management. It employs a quantitative explanatory approach. Primary data were collected via questionnaires distributed to 35 employees as samples using nonprobability sampling. Analysis involved multiple linear regression, t-test, F-test, and coefficient of determination. Results indicate that transparency in communication significantly influences GCG partially, while individual responsibility and accountability do not. Simultaneously, all three variables significantly affect GCG. From the Islamic HR Management perspective, low responsibility and accountability reflect suboptimal taqwa (god-consciousness), hisab (deed reckoning), and muhasabah dhatiyyah (self-accountability) to realize the amanah (trust) of khalifah (vicegerent).